Inflammatory mechanisms of ventilator‐induced lung injury: a time to stop and think?. (22nd November 2012) - Wilson, M. R.; Takata, M.
Summary Ventilator‐induced lung injury (VILI) is the phenomenon by which mechanical ventilation exacerbates lung injury in critically ill patients. It is particularly relevant for those suffering from acute respiratory distress syndrome, in which the iatrogenic injury caused by VILI contributes to their high mortality. The innate immune system is widely accepted to play an important role during VILI. However, it is our belief that the identification of inflammatory mediators that are crucial during VILI, and thus may make useful therapeutic targets, has become obscured by the wide variety of pre‐clinical animal models of VILI reported in the literature. We aim here to summarise some of our work addressing this issue over the last 10 years, and thus, we hope, make interpretation of a convoluted field a little clearer.